1841 Mich. Pub. Acts 29-30 - (:unkn) unknown (My University, 1841)
No. 18, §14: And the said common council shall have power . . . relative to the keeping and sale of gunpowder in said village[.]
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER